Nutrients balance for improvement of phytoremediation ability of teak seedlings (Tectona grandis) - Yavari, S. (Taylor and Francis Inc., 2018)
As a green technique, plant-based remediation systems can be used to remove nitrogen (N) pollutants from N-rich wastewaters. However, the excess amount of N and shortage of other nutrients in this system limits the plant growth and affects the plant remediation efficiency. In this study, the effect of adding phosphorus (P) and potassium (K) to the N-enriched wastewater on growth and N-removal efficiency of teak seedlings (Tectona grandis) was evaluated. Twelve ratios of N:P:K were applied to teak seedlings and the related effects were compared with those in control solution containing only N. The results indicated that a ratio of 1N:0.5P:1K increased dry matter accumulation in teak seedlings by improving the balance of nutrients in plants. Teak seedlings grown in nutritionally-improved system eliminated 33.8 N more than those grown in only N solution. The water loss through plant uptake was also enhanced in the improved system up to 56. Â© 2018 Taylor & Francis Group, LLC.